Promoting health : - Scriven, Angela (Palgrave, 2005)
This challenging and provocative book explores many contentious and debated issues associated with the promotion of health at a global level. The chapters offer insights into the key determinants of health between and within countries; how effective health promotion is in achieving health gain at a global level and the significant health challenges to be faced in the twenty-first century. The contributors are a highly distinguished group of academics and health professionals from around the world, including representatives from the World Health Organization, The International Union of Health Promotion and Education and the World Bank.